2022
DOI: 10.1093/braincomms/fcac049
|View full text |Cite
|
Sign up to set email alerts
|

Brain network topology early after stroke relates to recovery

Abstract: Analyses of alterations of brain networks have gained an increasing interest in stroke rehabilitation research. Compared to functional networks derived from resting-state analyses, there is limited knowledge of how structural network topology might undergo changes after stroke and, more importantly, if structural network information obtained early after stroke could enhance recovery models to infer later outcome. The present work re-analysed cross-sectional structural imaging data, obtained within the first tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The rational for this approach was that previous studies have found that patients with complete or almost complete recovery were found to exhibit much weaker relationships between brain structure and outcome 34 , 35 and that structure–outcome relationships might be particularly driven by more impaired patients and might not generalize to patients with minor deficits. 36 Table 1 summarizes the demographic and clinical data.…”
Section: Methodsmentioning
confidence: 99%
“…The rational for this approach was that previous studies have found that patients with complete or almost complete recovery were found to exhibit much weaker relationships between brain structure and outcome 34 , 35 and that structure–outcome relationships might be particularly driven by more impaired patients and might not generalize to patients with minor deficits. 36 Table 1 summarizes the demographic and clinical data.…”
Section: Methodsmentioning
confidence: 99%
“…Stroke lesions were semi-automatically delineated with SNAP-ITK 29 and available from our previous analyses [26][27][28]30 . The resulting lesion masks were registered to a 1-mm 3 Montreal Neurological Institute (MNI) template.…”
Section: Quantification Of Structural Disconnectionmentioning
confidence: 99%
“…7 However, from a systems neuroscience perspective, WMH may impact recovery trajectories by affecting large-scale structural and functional brain networks 9,10 as numerous studies have consistently reported that the state of structural brain networks, quantified early after acute stroke, can inform about subsequent recovery. [11][12][13] WMH-related network damage could serve as a surrogate for pre-existing disturbances in brain networks, and it could be a novel approach to better understand the underlying mechanisms of brain reserve capacity 14 and outcome variability after stroke, as recently evidenced for cortical and cerebellar brain anatomy. 15,16 The present study sought to answer the question whether the extent of WMH-related network damage, quantified early after severe ischemic stroke, can explain outcome variability.…”
Section: Introductionmentioning
confidence: 99%